Organocatalytic Transfer Hydrogenation of Cyclic Enones - Tuttle, Jamison B; Ouellet, Stéphane G; MacMillan, David W. C (Journal of the American Chemical Society, 2006)
The first enantioselective organocatalytic transfer hydrogenation of cyclic enones has been accomplished. The use of iminium catalysis has provided a new organocatalytic strategy for the enantioselective reduction of β,β-substituted α,β-unsaturated cycloalkenones, to generate β-stereogenic cyclic ketones. The use of imidazolidinone 4 as the asymmetric catalyst has been found to mediate the hydrogenation of a large class of enone substrates with tert-butyl Hantzsch ester serving as an inexpensive source of hydrogen. The capacity of catalyst 4 to enable enantioselective transfer hydrogenation of cycloalkenones has been extended to five-, six-, and seven-membered ring systems. The sense of asymmetric induction is in complete accord with the stereochemical model first reported in conjunction with the use of catalyst 4 for enantioselective ketone Diels−Alder reactions.